Numerical and experimental investigations of heat transfer enhancement in circular tubes with transverse twisted-baffles - Nanan, K.; Piriyarungrod, N.; Thianpong, C.; Wongcharee, K.; Eiamsa-ard, S. (My University, 2016)
Transverse twisted-baffles (T-TBs) and transverse baffles (TBs) were employed for heat transfer enhancement in circular tubes. The experimental and numerical studies were carried out to investigate heat transfer, friction loss and thermal performance factor associated with the use of the baffles (T-TBs/TBs). The studies encompass three different baffle width ratios (w/D = 0.1, 0.2 and 0.3, for TBs and T-TBs), three baffle twist ratios (y/w = 2.0, 3.0 and 4.0, for T-TBs) and Reynolds numbers from 6000 to 20,000. The experimental results reveal that at similar conditions, thermal performance factors of the tubes with the T-TBs are consistently higher than those of the ones with the TBs. This is attributed to the superior heat transfer enhancement with lower pressure drop penalty as the beneficial effects given by the T-TBs, as compared to those given by the TBs. For T-TBs, thermal performance factor increases as baffle width ratio (w/D) increases and twist ratio (y/w) decreases. The T-TBs with the smallest twist ratio (y/w = 2.0) give higher thermal performance factors than the ones with 3.0 and 4.0 by around 4.7–6.1 and 10.2–15 %, respectively. For the studied range, the T-TBs with the optimal geometric parameters, (y/w = 2.0 and w/D = 0.3), give the thermal performance factors in a range of 1.46–1.69.